Produção de suporte cerâmico poroso para a redução de material particulado da indústria cerâmica vermelha - Huanca, Karina Zuñiga (2013)
The processing of ceramic materials which involves burning of the bricks and other ceramic product red ceramic industries is associated with the release of gaseous components and particulate material in high concentrations that affect the environment and human health, considering that the gases emitted by these industries are not mostly treated before being released to the atmosphere. The purpose of this research was to develop a ceramic support with the main objective of the removal of particulate matter. Was used diatomaceous earth residue, ignimbrita (Sillar) and the bentonite as a binder, which possess a high amount of silica. The silica exists in two crystalline forms: quartz, cristobalite. The residue, diatomaceous earth, collected in a beer industry, was submitted to a thermal treatment for the elimination organic matter absorbed during filtration. The raw materials were subjected to chemical and mineralogical analysis by XRF and XRD. Were processed by the replication method. The Polymeric foams were immersed in the ceramic suspension (diatomite, ignimbrita, bentonite and water), and then dried and heat-treated for consolidation. The polymer foam was burned out at 400 °C and sintering was carried out at 1100 °C for 45 - 60 min. We‟re working four formulations with two variables, grain size and composition. The four formulations (10% diatomite and 16% ignimbrita) was more excellent, mechanical strength compresao of 0,8MPa and porosity of 81%. The reduction of particulate matter after using the ceramic support was approximately 84% and carbon monoxide was 72% is within the standards established by the Resolution n°382/2006 do CONAMA.